2009
DOI: 10.3174/ajnr.a1451
|View full text |Cite
|
Sign up to set email alerts
|

Noncontrast CT in Deep Cerebral Venous Thrombosis and Sinus Thrombosis: Comparison of its Diagnostic Value for Both Entities

Abstract: BACKGROUND AND PURPOSE:With its highly variable clinical presentation, the diagnosis of cerebral venous sinus thrombosis (SVT), and especially of deep venous thrombosis (DVT), as rare but important causes of stroke is challenging. Because noncontrast cranial CT (NCCT) is still the imaging technique of choice in most emergency departments, we aimed to investigate its value in the diagnosis of SVT and DVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
88
3
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 34 publications
(67 reference statements)
2
88
3
1
Order By: Relevance
“…Cord sign appears as increased density of the cerebral vein or sinus and is caused by increased attenuation of the thrombotic material in the affected vessel or sinus on CT. 15,23,24) However, findings of cord sign on CT have low sensitivity and specificity for the diagnosis of CVT, because flowing venous blood often appears to be hyperattenuated, especially in young people. 23) Furthermore, the sinuses are located next to the skull, so partial volume effects can result in a false-positive cord sign.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cord sign appears as increased density of the cerebral vein or sinus and is caused by increased attenuation of the thrombotic material in the affected vessel or sinus on CT. 15,23,24) However, findings of cord sign on CT have low sensitivity and specificity for the diagnosis of CVT, because flowing venous blood often appears to be hyperattenuated, especially in young people. 23) Furthermore, the sinuses are located next to the skull, so partial volume effects can result in a false-positive cord sign.…”
Section: Discussionmentioning
confidence: 99%
“…23) Furthermore, the sinuses are located next to the skull, so partial volume effects can result in a false-positive cord sign. 15,23) On the other hand, modern multidetector row CT scanners have greatly increased the value of the cord sign on CT in the emergency diagnosis of deep CVT. 15,24) Recent reports indicate that T 2 *-weighted imaging is one of the most useful MR sequences for the diagnosis of CVT because red thrombus appears as abnormally hypointensity in the acute phase due to the magnetic susceptibility of deoxyhemoglobin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 It is accepted as a useful technique to decide on further imaging and is reported to have a sensitivity and specificity of 64.6% and 97.2%, respectively, in the detection of CVST. 3,4 The attenuation of blood on unenhanced CT scans is predominantly caused by the protein factor of hemoglobin within the red blood cells. As a result, a linear relationship existed between the attenuation of blood and hemoglobin and HCT levels in a large series of 166 patients.…”
Section: Abbreviationsmentioning
confidence: 99%
“…11 With thinner CT sections, however, this sign was detected much more frequently. A more recent study 4 reported a significantly higher sensitivity (64%) of the hyperattenuated dural sinus sign for CVST. The authors included subacute and chronic cases, and it is known that the attenuation of a thrombus decreases as time passes, resulting in possible false-negative imaging findings on unenhanced CT scans.…”
mentioning
confidence: 99%